2014
DOI: 10.14719/pst.2014.1.4.79
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path coefficient analysis between yield and yield components in potato (Solanum tuberosum L.)

Abstract: The associations of yield and its components offer important information in breeding plants. A study was conducted at the Araka Agricultural Research Center, Hossana, Ethiopia during 2012 growing season under rain fed condition on 18 potato genotypes/varieties to determine the association of yield and its components. The association was analyzed by correlation coefficient, and further subjected by path coefficient analysis to estimate direct and indirect effects of each character on tuber yield. Positive and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Hossain et al (2000) reported positive direct genotypic effects of tuber yield per plant, average tuber weight and harvest index on total tuber yield. This is in line with Abraham et al (2014) who too indicated stem number per plant, plant height and average tuber weight had positive direct effect on tuber yield. Hence, these traits will be given due consideration during selection.…”
Section: Path Coefficient Analysissupporting
confidence: 85%
“…Hossain et al (2000) reported positive direct genotypic effects of tuber yield per plant, average tuber weight and harvest index on total tuber yield. This is in line with Abraham et al (2014) who too indicated stem number per plant, plant height and average tuber weight had positive direct effect on tuber yield. Hence, these traits will be given due consideration during selection.…”
Section: Path Coefficient Analysissupporting
confidence: 85%
“…The Tytanit ® application caused an increase in the tuber weight per plant, which was confimed in a study carried out in southeast Lithuania on Haplic Luvisol [Asakaviciute and Lisova 2009]. A positive correlation was found between the tuber yield and the tuber weight per plant [Abraham et al 2014, Darabad 2014. The tuber weight per plant in the greater extent depended on the date of Tytanit ® application than on the Tytanit ® dose.…”
Section: Discussionmentioning
confidence: 74%
“…in the leaf development stage and with repeated treatment in the tuber formation stage), the plants were shorter and the weight of their stems was lower. A positive correlation was found between the tuber yield and the plant height, stems per plant and main stem diameter [Arslan 2007, Abraham et al 2014, Darabad 2014.…”
Section: Discussionmentioning
confidence: 92%
“…In a study carried out in southeast Lithuania on Haplic Luvisol, the tuber weight per plant was greatest with two Tytanit ® applications (at the beginning of crop cover BBCH 31 and at the beginning of flowering BBCH 60-62) in the dose of 0.2 dm 3 * ha -1 and liquid complex microelements fertilizers of differing composition (Asakavičiūtė and Lisova, 2009). A positive correlation was found between the tuber yield and the tuber number and tuber weight per plant (Abraham et al, 2014;Darabad, 2014). The potential number of tubers may be determined by the number of stolons and the environmental conditions affecting stolon formation and development (Wurr et al, 1997).…”
Section: Discussionmentioning
confidence: 99%